Bioblitz! : counting critters - Edwards Richmond, Susan (Peachtree Publishing Company, 2022)
You might be amazed at the large number of insects, birds, and small mammals that inhabit even a very small plot of land. In this story Gabriel's dad, a ranger for the local municipal park, is helping with a Biodiversity Day (or Bioblitz), and he invites Gabriel and his cousin Ava to participate. With Gabriel's expertise in bugs and Ava's eye for birds, the two cousins are eager to start the hunt in the park. They are placed on different teams, competing to see which group finds the most species of animal life in the time allotted.